COOPERATIVE READINESS FOR E-LEARNING - Lucia Istyowati; Tiolina Evi (Faculty of Computer Science Universitas Indonesia, 2015)
Cooperative is basically an economic organization of the people who have the economic capacity, which is in motion is not only concerned with economic motives. In addition to form a company that requires a profit, the cooperative also has a social motive. This is reflected in the principles espoused. Cooperative is an organization that is familial and managed democratically. In this study the chosen type of credit union, a group of people who agree to raise capital by providing loans to members of its own with a decent interest rate and approved. As one of the requirements in order to be able to make loans to members of cooperatives are the members must have attended training organized by the cooperative board. The spread of the location and the bustle complicate members required to attend training. Development of technology and beneficiaries among members provide alternative learning solutions for members. For that we need to know whether members are ready to accept the training system based on information technology. The readiness of members in this case at CU Melati Kopdit Jagakarta landfill checked by sampling techniques. From preliminary research/beginning it seems that members of the CU Melati landfill Jagakarsa ready to accept the program of distance education (elearning) for cooperative education.